2023
DOI: 10.3390/jcm12041372
|View full text |Cite
|
Sign up to set email alerts
|

How Radiomics Can Improve Breast Cancer Diagnosis and Treatment

Abstract: Recent technological advances in the field of artificial intelligence hold promise in addressing medical challenges in breast cancer care, such as early diagnosis, cancer subtype determination and molecular profiling, prediction of lymph node metastases, and prognostication of treatment response and probability of recurrence. Radiomics is a quantitative approach to medical imaging, which aims to enhance the existing data available to clinicians by means of advanced mathematical analysis using artificial intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 115 publications
(174 reference statements)
0
14
0
Order By: Relevance
“…The various radiomics features used are shape features, first-order histogram-based features, second-order texture features, and higher-order transform-based features. 38 Fusion of deep features and radiomic features can improve the efficiency in BC detection and classification.…”
Section: Radiomics and Deep Learning-based Cad Approaches For Breast ...mentioning
confidence: 99%
“…The various radiomics features used are shape features, first-order histogram-based features, second-order texture features, and higher-order transform-based features. 38 Fusion of deep features and radiomic features can improve the efficiency in BC detection and classification.…”
Section: Radiomics and Deep Learning-based Cad Approaches For Breast ...mentioning
confidence: 99%
“…Recent studies suggested that the application of radiomics in mammography could produce significant results in the diagnosis of breast cancer. In 2019, in the study by Li et al [ 48 ], the extraction of quantitative features from the analysis of the mammograms of 182 patients proved to be better than simple qualitative analysis of the lesion [ 49 ]. Furthermore, from the study by Tagliafico et al [ 50 ], also conducted in 2019, on 40 patients with high breast density, it was shown that the use of radiomics in tomosynthesis was useful in differentiating malignant findings from normal breast tissue [ 49 ].…”
Section: Radiomicsmentioning
confidence: 99%
“…Radiomics, a burgeoning field within medical imaging, involves the extraction and analysis of a vast array of quantitative features from medical images [1][2][3][4][5][6]. These features encompass a wide range of information, capturing subtle and complex patterns that may not be discernible to the human eye alone [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These features encompass a wide range of information, capturing subtle and complex patterns that may not be discernible to the human eye alone [6][7][8][9][10][11]. Radiomics has garnered significant attention due to its potential to provide valuable insights for personalized medicine, treatment response prediction, and disease diagnosis [3,4,8,9,12]. However, the inherent variability in image acquisition protocols, equipment, and analysis techniques has led to a pressing need for standardized methodologies and benchmarking in radiomics research [13,14].…”
Section: Introductionmentioning
confidence: 99%